Search for sleptons in e+e- collisions at centre-of-mass energies up to 184 GeV ALEPH Collaboration - BARATE, R. (Institutional Knowledge at Singapore Management University, 1998)
The data collected by the ALEPH experiment at LEP at centre–of–mass energies around 183 GeV are analysed to search for sleptons, the partners of leptons in supersymmetric theories. The previously published search for acoplanar leptons and missing energy has been updated. New searches have been developed to cover a wider range of slepton signals. These include single electrons, acoplanar leptons accompanied by two photons plus missing energy as well as particles with lifetime. No evidence for the production of any such particles is found. Slepton mass limits are reported within gravity mediated and gauge mediated SUSY breaking scenarios.